Use of Potato as an Alternative Source of Carbohydrate in Tilapia (Oreochromis Niloticus) Fish Feed (Annals of Bangladesh Agriculture, 2020)
The study was conducted to evaluate the potentiality of potato as an alternative source of carbohydrate in fish feed and its effect on the growth performance, glucose level and survivability of tilapia (Oreochromis niloticus). The experiment was designed into four treatments with three replications in each including control T1 (feed without rice bran and potato), T2 (feed with rice bran), T3 (feed with raw potato) and T4 (feed with boiled potato). Tilapia fry (average 6.27±0.07 g) were randomly distributed in each treatment as 40 fish per 300L tank and feed with experimental diets (protein 35%). Significantly higher (P